Comparison of dermatoglyphic patterns between children with and without Down syndrome - Nitra Syafa Irzika; Mala Kurniati; Zulhafis Mandala; Astri Pinilih (JOURNAL OF Medical Surgical Concerns, 2026)
Background: Dermatoglyphic patterns develop during embryogenesis and are influenced by genetic and intrauterine factors. Trisomy 21 may alter epidermal ridge formation, making fingerprint patterns a potential non-invasive supportive marker of developmental variation. Purpose: To compare participant-level categorical fingerprint patterns between children with and without Down syndrome. Method: This comparative cross-sectional study included 59 participants: 29 children with Down syndrome and 30 children without Down syndrome. Fingerprint impressions were obtained using an ink pad and fingerprint paper, and each child was assigned one participant-level category (loop, whorl, or arch). Fisher's exact test compared the loop and whorl distributions because no arch patterns were observed; p < 0.05 was considered statistically significant. Results: Loop patterns were reported in 23 children with Down syndrome (79.3%) and 27 children without Down syndrome (90.0%). Whorl patterns were reported in 6 children with Down syndrome (20.7%) and 3 children without Down syndrome (10.0%); no arch patterns were identified. The distribution was not significantly different between groups (p = 0.299). Conclusion: Participant-level loop, whorl, and arch pattern distributions were not significantly different between children with and without Down syndrome in this sample. These broad categories should not be interpreted as a stand-alone diagnostic marker.